Modelo digital do terreno lidar para caracterização topográfica e de redes de drenagem - Mendonça, Rafael Lopes (2022)
The Digital Elevation Model (DEM) is an important data source for several areas, such as ecology, hydrology, archeology and renewable energy. Especially for hydrology, by processing this data it is possible to obtain the drainage network, watershed delimitation, topographic characterization, longitudinal and transversal profiles, for example. With the advancement of data acquisition systems, including Light Detection and Ranging (LiDAR), models with increasingly detailed spatial resolutions have become available. The increase in spatial resolution has an impact on the increase in storage and processing costs, as it makes it difficult or impossible to use conventional algorithms for automatic drainage network extraction. For these reasons, it is necessary to adapt the algorithms to be able to handle large amounts of data. Another contour measure consists of the degradation of the spatial resolution, which can be done through resampling or through the upscaling of flow directions, for example. Such factors justify the analysis of the impact of using high spatial resolution data from LiDAR, compared to data with degraded spatial resolutions, in the automatic extraction of the drainage network. In addition to the impact of the methods used in the extraction of the drainage network and in the degradation of the DEM, resampling and upscaling. In this research, the 1 m DTM LiDAR data were used, this data resampled to 2, 5, 10 and 30 m, the upscaling of flow directions from the original data from 1 m to 30 m, and the DEM SRTM, as it is a data widely used in the literature. The SRTM presents inferior results when compared to all the processing performed using the DTM LiDAR. Furthermore, the SRTM can present a significant failure to extract drainage.. The results also reveal that the resampled data are inferior to the upscaling of flow directions, having as reference the drainage network obtained through processing the 1 m DTM LiDAR data.